Nahdlatul Ulama dan Praktik Deradikalisasi di Media Online - Said Romadlan (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2022)
This study focuses on deradicalization practices carried out by Nahdlatul Ulama (NU) through NU Online media (nu.or.id), to dismantle power relations in deradicalization practices in particular. The research method uses Foucault's Critical Discourse Analysis, which emphasizes two elements, namely discourse practice and dominant-marginal discourse. The results of the study show, first, deradicalization has become the dominant discourse in nu.or.id as the right measure to overcome radicalism. Deradicalization practices at NU's online media are carried out by proposing deradicalization regional regulations (Raperda), workshops and seminars, reciting Kitab, and meetings of interfaith leaders. Second, the power relations in deradicalization practices carried out by NU are influenced by NU's power relations with the government. The results of this study confirm the existence of a strategic role for NU's online mediain in disseminating the idea of deradicalization to overcome radicalism in Indonesia.